1998
DOI: 10.1073/pnas.95.13.7502
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel susceptibility loci for inflammatory bowel disease on chromosomes 1p, 3q, and 4q: Evidence for epistasis between 1p and IBD1

Abstract: The idiopathic inf lammatory bowel diseases, Crohn's disease (CD) and ulcerative colitis (UC), are chronic, frequently disabling diseases of the intestines. Segregation analyses, twin concordance, and ethnic differences in familial risks have established that CD and UC are complex, nonMendelian, related genetic disorders. We performed a genome-wide screen using 377 autosomal markers, on 297 CD, UC, or mixed relative pairs from 174 families, 37% Ashkenazim. We observed evidence for linkage at 3q for all familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
255
7
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(272 citation statements)
references
References 30 publications
8
255
7
2
Order By: Relevance
“…Chromosome 1q43-44 has been implicated in a genome screen of rheumatoid arthritis 25 as well as in three independent studies of systemic lupus erythematosus. [26][27][28] Chromosome 16q24 also showed evidence of linkage in inflammatory bowel disease 29 as well as two independent screens of rheumatoid arthritis, 25,30 and the region on 4q24 showed the strongest evidence of linkage outside the HLA region in a genome screen of rheumatoid arthritis. 25 In addition, the region of suggestive linkage on chromosome Xp11 overlaps with a region linked to insulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 92%
“…Chromosome 1q43-44 has been implicated in a genome screen of rheumatoid arthritis 25 as well as in three independent studies of systemic lupus erythematosus. [26][27][28] Chromosome 16q24 also showed evidence of linkage in inflammatory bowel disease 29 as well as two independent screens of rheumatoid arthritis, 25,30 and the region on 4q24 showed the strongest evidence of linkage outside the HLA region in a genome screen of rheumatoid arthritis. 25 In addition, the region of suggestive linkage on chromosome Xp11 overlaps with a region linked to insulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 92%
“…Chromosome region 1q31 has been implicated in linkage studies in lupus and multiple sclerosis (22)(23)(24). Multiple investigations have suggested linkage for chromosome region 1p36 in lupus (24)(25)(26), celiac disease (27), inflammatory bowel disease (28), and RA (29,30). This region was delineated further in adult RA using a case-control association design of single-nucleotide polymorphisms, resulting in a functional haplotype associated with RA that includes the gene PADI4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Crohn disease is an example. Independent ASP studies suggested that several possible loci on different chromosomes were involved in Crohn disease [82][83][84] . Many, but not all, studies implicated a locus on chromosome 16; some of these studies, on their own, barely highlighted this region.…”
Section: Asp Studiesmentioning
confidence: 99%